Interdependensi Antara Kepemilikan Manajerial, Dividen, Investasi, dan Nilai Perusahaan - Moningka, Petrus (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
This research uses simultaneous regression in order to examine interdependent correlation between structure of ownership, financial decision, and firm value , by using four endogenous variables namely managerial ownership, dividend policy, investment decision, and firm value . This research tries to explain how is the interconnection of the policies on the companies categorized as LQ-45 in Indonesia. This research uses four regression models, by employing managerial ownership and dividend policy as a mechanism to suppress conflict of interests between managers and principals with regard to the company’s objective to increase the value of the company. Jensen and Meckling (1976) state that agency problem arises due to the separation between ownership and control. Population of this research is companies listed in the Indonesian Stock Exchange (BEI) within the category of LQ-45, with the use of purposive sampling method. There are 23 companies, using data pooling and two stage least square (2SLS) in the data analysis.  Findings of this research in a whole shows that there is an interdependent relationship between managerial ownership, dividend policy, investment decision, and firm value. The result of this research also finds the substitutive relationship among managerial ownership and dividend policy in suppressing agency conflicts.